Proposição de um framework teórico-empírico para gestão de riscos na cadeia de suprimentos sustentável - Souza, Thiago Alves de (Universidade Federal de São Carlos, 2019)
Over the past few years, organizations have sought to integrate the different aspects of sustainability into their business by addressing environmental, social and economic issues more effectively. An efficient way to implement sustainability in operations can be through the sustainable management of your supply chains. Sustainable supply chains, however, are exposed to a number of risks, such as unsustainable supplier behavior, characterization of a bad public image, workplace accidents, environmental contamination, reputational and image loss, among other issues that may negatively affect your performance. The relationship between the sustainable supply chain and risk management has been pointed by several authors as a conducive area for research. Thus, aiming to fill the gap on the joint theme, the aim of this study is to build a model for sustainable supply chain risk management. To build the theoretical framework, a systematic literature review with 150 articles was performed. Eleven risk source categories were created and 69 risk types were found, in addition to surveying 28 types of mitigation strategies in 4 categories. From an empirical point of view, a unique Case Study was conducted in conjunction with the Critical Incident Technique in a beverage industry. Semi-structured interviews were conducted with 18 respondents from the organization and the information obtained was treated through Content Analysis in the QSR Nvivo 11 software. The results presented discuss the types of risks found that were transportation, laws, standards and regulations, supplies and environment. It was also noted that the organization assesses risk based on the probability and impact criteria. The case study made it possible to survey 51 types of mitigation strategies that were allocated into 22 categories. The organization also develops risk learning by highlighting the key lessons learned in the event of a completed occurrence. Finally, an expanded theoretical-empirical model has been built that enables supply chains to become increasingly sustainable as they have a risk management orientation, thus achieving a number of benefits such as increased preparedness and reduced risk. vulnerability.
Proposition of a theoretical-empirical framework for sustainable supply chain risk management
Propuesta de un marco teórico-empírico para la gestión sostenible del riesgo de la cadena de suministro
Keywords: Gestão sustentável da cadeia de suprimentos; Processo de gestão de riscos; Framework; Identificação de risco; Mitigação de risco; Sustentabilidade; Sustainable supply chain management; Risk management process; Model; Identification of risk; Risk mitigation; Sustainability; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DA PRODUCAO; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO